2002
DOI: 10.1046/j.1439-0450.2002.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subminimal Inhibitory Concentrations of Amoxicillin againstActinobacillus pleuropneumoniae

Abstract: The bactericidal effects of amoxicillin at below minimum inhibitory concentration (MIC) against Actinobacillus pleuropneumoniae NB001 were studied in vitro and in vivo. In vivo, the efficacy of amoxicillin on experimentally induced A. pleuropneumoniae infection in disease-free pigs was evaluated. Nine pigs were divided into three groups and all three groups were housed in the same room. Group I pigs were given long-acting amoxicillin injection 22 h prior to A. pleuropneumoniae challenge. Group II pigs were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Regarding the respiratory bacteria, both P. multocida and A. pleuropneumoniae showed clear ECOFFs at 1.0 μg/ml and 0.5 μg/ml, respectively, and potentially resistance rates of 2.6% and 11.3%, respectively, above their ECOFFs (El Garch et al., ). Tanigawa and Sawada () showed that there was a sub‐MIC inhibitory effect at a quarter of the MIC for a particular strain of A. pleuropneumoniae , which disappeared when the amoxicillin was inactivated. At 1.25 times the MIC, there was a bactericidal effect seen even after 2 hours (hr).…”
Section: Pharmacodynamics Of Amoxicillinmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the respiratory bacteria, both P. multocida and A. pleuropneumoniae showed clear ECOFFs at 1.0 μg/ml and 0.5 μg/ml, respectively, and potentially resistance rates of 2.6% and 11.3%, respectively, above their ECOFFs (El Garch et al., ). Tanigawa and Sawada () showed that there was a sub‐MIC inhibitory effect at a quarter of the MIC for a particular strain of A. pleuropneumoniae , which disappeared when the amoxicillin was inactivated. At 1.25 times the MIC, there was a bactericidal effect seen even after 2 hours (hr).…”
Section: Pharmacodynamics Of Amoxicillinmentioning
confidence: 99%
“…The LA formulation appears to go below by 24 hr (Agersø & Friis, 1998a) (see Figure 2). Other LA formulations (Tanigawa & Sawada, 2002) lasted over 36 hr. Both the LA formulation's amoxicillin concentrations were above the MIC 90 for S. suis of 0.06 μg/ml for 48 hr, at 0.07 and 0.15 μg/ml, respectively.…”
Section: Pharmacokinetics Of Amoxicillin By Route Of Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a long PAE was described as well for H. influenzae isolates and amoxicillin-clavulanate (Thorburn and Moleswoth 1992). This observation might explain the already described strong sub-MIC effect of amoxicillin in an in vitro and in vivo study where it prevented 100% mortality of pigs in controls challenged by A. pleuropneumoniae and non-treated groups (Tanigawa and Sawada 2002).…”
Section: Discussionmentioning
confidence: 54%
“…, 1999; Marie et al. , 2002; Tanigawa & Sawada, 2002). When applied in vivo to pigs, AMO showed high activity against pathogens commonly seen in respiratory and digestive tracts, including Actinobacillus pleuropneumoniae (Agerso & Friis, 1998a; Lauritzen et al.…”
Section: Introductionmentioning
confidence: 99%